Hydrothermal synthesis of calcium sulfoaluminate–belite cement from industrial waste materials. (1st March 2016) - Rungchet, A.; Chindaprasirt, P.; Wansom, S.; Pimraksa, K.
Abstract: This study investigated the use of industrial waste materials viz., fly ash, Al-rich sludge and flue gas desulfurization gypsum in the production of calcium sulfoaluminate–belite cement using hydrothermal–calcination method. The lime deficit in the waste starting materials was recompensed by the addition of hydrated lime. Various factors viz., type of hydrothermal solvent, time of hydrothermal process and calcinations temperature of the hydrothermal products were studied. Phase developments during various synthesized conditions were studied using X-Ray Diffraction. The cement products were mixed with 20 wt% flue gas desulfurization to allow ettringite formation for solidification. The hydration development was investigated in terms of mineralogical composition, microstructures and compressive strength of the hydration products. The largest numbers of calcium sulfoaluminate–belite cement could be obtained by calcination at temperature of 1050 °C. The synthesized cement developed an acceptable 28-day compressive strength of 30.0 MPa. The main hydration products were ettringite, portlandite, calcium silicate hydrate and calcium aluminosilicate hydrate resulting from the hydration of calcium sulfoaluminate and belite phases. Highlights: Calcium sulfoaluminate–belite (CŜAB) cement was prepared via hydrothermal–calcination. Non-alkaline activated CŜAB cement provided yeelimite as main phase. Alkaline activated CŜAB cement provided yeelimite, belite and mayenite. Non-alkaline activated cement developed strength better than alkaline activated system.